Health Information Use Among Healthcare Providers: A Systematic Review - Almutairi, Bandar Menwer Munawir; Sarhan, Naif Saad Nasser Al; Alruwaili, Ebtesam; Alshalawi, Awwadh Ghazi; Alotaibi, Nasser Meshal Thamer; Jaha, Amro Abdulathim; Salman Dhawi Al Otaibi; Rabee Ahmad Mohmaad Alshareef; Jumana Abdulmohsen Mohammed Almulhim; Soad Hassan Alfahmi; Abdullah Aziz Almalky (Migration Letters, 2023)
Background: Healthcare policy formulation, program planning, monitoring and evaluation, and healthcare service delivery as a whole are dependent on routinely generated health information in a healthcare setting. Having a reliable source for health information is vital to build a strong foundation of knowledge, especially with the current revolution of the internet and social media, which raises many concerns regarding harmful effects on the health of the public. However, there are no studies on how the Saudi Arabian population seeks health information. Details about the most used and trusted sources of health information among the public will help health authorities and public awareness accounts on social media to effectively disseminate health information. Aim: The main aim of this review was to combine the magnitude of routine health information use and its determinants among healthcare providers. Methods: Databases and repositories such as PubMed, Global Health, Scopus, Journal online, Advanced Google Search and Google Scholar were searched until August 2022. Result: A total of 890 articles were searched but only 23 articles were included. A total of 8662 (96.3%) participants were included in the studies. The pooled prevalence of routine health information use was found to be 53.7% with 95% CI (47.45% to 59.95%). Training (adjusted OR (AOR)=1.56, 95% CI (1.12 to 2.18)), competency related to data management (AOR=1.94, 95% CI (1.35 to 2.8)), availability of standard guideline (AOR=1.66, 95% CI (1.38 to 1.99)), supportive supervision (AOR=2.07, 95% CI (1.55 to 2.76)) and feedback (AOR=2.20, 95% CI (1.30 to 3.71)) were significantly associated with routine health information use among healthcare providers at p value≤[1]0.05 with 95% CI. Conclusion: The use of routinely generated health information for evidence-based decision-making remains one of the most difficult problems in the health information system. The study’s reviewers suggested that the appropriate health authorities invest in enhancing the skills in using routinely generated health information.